Droppers as a tool of cybercrime: history, functions, and challenges for law enforcement agencies (Journal of actual problems of jurisprudence, 2025)
The rapid development of digital technologies has led to the emergence of new forms of cyber threats, among which the phenomenon of “droppers” occupies a special place. In academic and practical literature, this term is used in two senses: first, as a software component designed to deliver and activate other malicious modules; second, as individuals or groups of individuals through whom illicit funds, documents, or other objects of criminal activity are channeled. This dual understanding makes the study of droppers both relevant and necessary for building a comprehensive system of legal response.The purpose of this study is to provide a comprehensive analysis of droppers as a tool of cybercrime, to identify their functions and historical evolution, and to determine the challenges they pose to the law enforcement agencies of the Republic of Kazakhstan. The main focus of the research lies in comparing the software and social forms of droppers, examining their role in concealing the sources of criminal activity, and identifying the legal difficulties of their qualification.The scientific and practical significance of the study lies in the fact that the consideration of droppers allows for a fresh perspective on the mechanisms of cybercriminal schemes and contributes to the development of recommendations for improving legislation and investigative practice. The methodological framework of the research is based on general scientific methods of analysis, synthesis, systemic and comparative-legal approaches, as well as the historical-legal method applied to study the genesis of the phenomenon.The findings confirm that droppers play a key role in complicating the disclosure of cybercrimes by creating a gap between perpetrators and ultimate beneficiaries. The study proposes measures to strengthen technical oversight, improve legal regulation, and raise the level of public legal awareness.The contribution of this research lies in expanding the theoretical understanding of cyber threats and in developing proposals that can be practically applied in the activities of the law enforcement bodies of the Republic of Kazakhstan.Keywords: droppers, cybercrime, intermediaries, information technologies, legal regulation, digital security.